2019
DOI: 10.1007/s10753-019-01084-0
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of NADPH Oxidase-Derived Reactive Oxygen Species Decreases Expression of Inflammatory Cytokines in A549 Cells

Abstract: Various experimental models strongly support the hypothesis that airway inflammation can be caused by oxidative stress. Inflammatory airway diseases like asthma and COPD are characterized by higher levels of ROS and inflammatory cytokines. One of the sources of ROS is NADPH oxidase. Therefore, the aim of the study was to investigate influence of NADPH oxidase inhibition on the expression of IL-6, IL-8, TNF, TSLP, CD59, and PPAR-γ in vitro. A549 cells were incubated with apocynin in three concentrations (0.5 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 85 publications
0
13
0
Order By: Relevance
“…The AV protective action against UV radiation was due to its stimulating effect on SIRT1 activity (Liu et al, 2020). Moreover, the in vitro activity of AV on PPARγ activity was significantly recognized by Wieczfinska, Sitarek, Skała, Kowalczyk, and Pawliczak (2019), who explore the anti-inflammatory activity of AV is mediated by the activation of PPARγ protein expression. Furthermore, the antioxidant activity of AV was also endorsed by the study conducted by Hassanein, Abd El-Ghafar, et al (2020), who stated that AV has a potential cardioprotective effect through the up-regulation of many antioxidant defense mechanisms, including Nrf2 and cytoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…The AV protective action against UV radiation was due to its stimulating effect on SIRT1 activity (Liu et al, 2020). Moreover, the in vitro activity of AV on PPARγ activity was significantly recognized by Wieczfinska, Sitarek, Skała, Kowalczyk, and Pawliczak (2019), who explore the anti-inflammatory activity of AV is mediated by the activation of PPARγ protein expression. Furthermore, the antioxidant activity of AV was also endorsed by the study conducted by Hassanein, Abd El-Ghafar, et al (2020), who stated that AV has a potential cardioprotective effect through the up-regulation of many antioxidant defense mechanisms, including Nrf2 and cytoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al reported that APO inhibited the production of proinflammatory cytokines including TNF‐α, IL‐1β, and IL‐6 in experimental asthma mice 18 . Similarly, recent studies have demonstrated that APO decreased TNF‐α and IL‐1β gene expression or downregulation of these cytokines through experimental animal studies or cell cultures on the different inflammatory lung diseases 17,24,45,46 . NOX is an enzyme responsible for ROS production, and proinflammatory stimulus induces intracellular ROS via enzymatic activation of NOX, which ultimately induces activation of NF‐κB 47,48 .…”
Section: Discussionmentioning
confidence: 98%
“… Bowen et al (2017a) found that exercise training can reduce the activity of NOX in the diaphragm of mice with COPD, regulate the oxidative stress level, weaken protein degradation, reverse the extrapulmonary damage to the diaphragm caused by smoking, enhance the muscle strength of the diaphragm, and restore the diaphragm function. In addition, the study found that the oxidative stress produced by NOX may be closely related to the expression level of pro-inflammatory factors such as tumor necrosis factor (TNF), and the antioxidant effect was partly responsible for the decrease of the expression level of pro-inflammatory factors ( Wieczfinska et al, 2019 ). Blockage of TNF-α can significantly reduce the number of inflammatory cells and the production of superoxide anion in the diaphragm and improve the structure and function of the diaphragm ( Domínguez-Álvarez et al, 2014 ).…”
Section: Effect and Mechanism Of Exercise On Oxidative Stress Of The Diaphragm In Copdmentioning
confidence: 99%